The cleaning effect of sugar-free chewing gum on occlusal surfaces - Sindhu, Harpreet Kaur; Hartono, Sri Wendari; Sukartini, Endang (Padjadjaran Journal of Dentistry, 2012)
Introduction: Sugar-free chewing gum has the potential to provide oral health benefits including plaque control. This study benefit to develop and validate an occlusal site-specific plaque index. The index will be used to check the results of chewing sugar-free chewing gum. The purpose of this study is to analized the cleaning effect of sugar-free chewing gum on occlusal surfaces. Methods: The research is a split mouth design, single blind, cross over study. The research consists of 30 volunteers chosen by random sampling. Volunteers divided into two groups, each consisting of 15 volunteer’s. Group A, volunteers were asked to chewing gum on the left side regimen whereas volunteers in group B were asked to chew on the right side regimen for 5 minute period. After a minimum of 4 days washout period, the study was repeated with the volunteers’ crossing over to the alternative chewing right or chewing left regimen. Results:  The mean difference 0.224.Paired sample t-test was used to determine whether there are significant differences before and after chewing gum. With level of significance α=5 % the t-values for both groups are both 0.00.There are differences before and after chewing gum in group A and B. Conclusion: Sugar-free chewing gum have cleaning effect of on occlusal surfaces, sugar-free chewing gum decreases the plaque accumulation on occlusal surfaces.